Development of Deterministic-Stochastic Mathematical Models for Predicting Zoonotic Disease Transmission Dynamics in Tropical Regions - Khairunnisa Fadhilla Ramdhania (Science Journal Get Press, 2026)
Leptospirosis is a re-emerging zoonotic disease involving complex interactions between humans, animal reservoirs, and the environment. This study investigates leptospirosis transmission using a coupled human–rodent SIR–SIR model under deterministic and stochastic frameworks. The basic reproduction number ( ) was derived analytically to determine invasion thresholds. Deterministic analysis shows that when , the disease persists and converges to an endemic equilibrium. In contrast, stochastic simulations reveal substantial variability in transmission dynamics and demonstrate the possibility of disease extinction even under conditions that deterministically predict persistence. Sensitivity analysis identifies the rodent-tohuman transmission rate and human recovery rate as key parameters influencing . These findings highlight the limitations of purely deterministic models and emphasize the importance of stochastic approaches for capturing realistic zoonotic disease dynamics. The proposed framework provides insights for developing integrated control strategies combining reservoir management, environmental intervention, and early treatment.